2018
DOI: 10.6007/ijarped/v7-i3/4568
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perspective on Cultural Diversity in School: A Case Studies

Abstract: Malaysia is known as a multi-racial and multi-cultural. The many different ethnicities that currently exist in Malaysia have their own unique and distinctive cultural identities. This study aims to understand teachers' perspective on cultural diversity in primary schools based on Byram's multicultural model that focused on four aspects which are knowledge, skills, attitudes and practices. A qualitative approach with case study design was used in this study. The respondents involving three teachers and an admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…He also suggested that teachers need to be given professional training at the college level to encourage more trust in multicultural practices that should be nurtured from an early age. When teachers' positive perceptions of multiculturalism can be increased, the impact is on the field of education (Wahab et al, 2018;Arruzza & Chau, 2021;Aslan, 2019;Awang et al, 2017;Barsihanor et al, 2021).…”
Section: Variable Contribution Of Teaching Experience the Level Of Kn...mentioning
confidence: 99%
“…He also suggested that teachers need to be given professional training at the college level to encourage more trust in multicultural practices that should be nurtured from an early age. When teachers' positive perceptions of multiculturalism can be increased, the impact is on the field of education (Wahab et al, 2018;Arruzza & Chau, 2021;Aslan, 2019;Awang et al, 2017;Barsihanor et al, 2021).…”
Section: Variable Contribution Of Teaching Experience the Level Of Kn...mentioning
confidence: 99%
“…95% of teachers from both backgrounds use multiple ways of education methods. Different teaching pedagogies show the teacher's commitment and contribution in understanding the diverse culture of students and provide equal opportunity to all the students to learn in multicultural classrooms 30) .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internationally schools are increasingly characterised by a diverse, culturally complex student population (Civitillo, Schachner, Juang, van der Vijver, Handrick & Noack 2017;Wahab, Nathan, Hasnida, Ghazali, Rabi & Dawi 2018). Educational concepts across countries, also in Germany and South Africa, aim at implementing inclusive concepts to cater for this diversity (Schneider 2018;).…”
Section: Introductionmentioning
confidence: 99%